Cortical networks underlying successful control of nociceptive processing using real-time fMRI - Bucolo, Maide; Rance, Mariela; Nees, Frauke; Ruttorf, Michaela; Stella, Giovanna; Monarca, Nicolò; Andoh, Jamila; Flor, Herta (Frontiers in Pain Research, 2022)
Real-time fMRI (rt-fMRI) enables self-regulation of neural activity in localised brain regions through neurofeedback. Previous studies showed successful up- and down-regulation of neural activity in the anterior cingulate cortex (ACC) and the insula (Ins) during nociceptive stimulation. Such self-regulation capacity is, however, variable across subjects, possibly related to the ability of cognitive top-down control of pain. Moreover, how specific brain areas interact to enable successful regulation of nociceptive processing and neurofeedback-based brain modulation is not well understood. A connectivity analysis framework in the frequency domain was used to examine the up- or down-regulation in the ACC and Ins and pain-associated brain areas during nociceptive processing. It was found that successful up- and down-regulation is mediated by the ACC and by its functional connectivity with the Ins and secondary somatosensory cortex. These findings demonstrate functional interactions between brain areas involved in nociceptive processing during regulation of ACC and Ins activity, and the relevance of the frequency domain connectivity analysis for real-time fMRI.